The text of Paradise lost : a study in editorial procedure - Moyles, R. G. (Heritage., 1985)
This study traces the transmission history of the poem, Paradise Lost, from its first appearance in 1667, through the eighteenth century with its emphasis on conjectural criticism, to the present century when it was subjected to unwarranted 'restoration.'